A PK/PD study of Delta-4 abiraterone metabolite in metastatic castration-resistant prostate cancer patients. (October 2018) - Blanchet, Benoit; Carton, Edith; Alyamani, Mohammad; Golmard, Lisa; Huillard, Olivier; Thomas-Scheomann, Audrey; Vidal, Michel; Goldwasser, François; Sharifi, Nima; Alexandre, Jérôme
Graphical abstract: Abstract: Δ 4 -abiraterone (Δ4A) is an activemetabolite of abiraterone (ABI), which is approved in the treatment of metastatic castration resistant prostate cancer (mCRPC). The contribution of Δ4A to the clinical antitumor activity of ABI remains unknown. The aim of this study was to explore the relationship between plasma Δ4A concentration and survival in 36 mCRPC patients treated with abiraterone acetate (1000 mg/day) plus prednisone (10 mg/day). Plasma trough ABI and Δ4A concentrations were monthly assayed using liquid chromatography during the first 3 months of treatment. ABI and Δ4A Cmin were defined as the mean of trough concentrations measured for each patient. Predictive factors regarding progression-free survival (PFS) and overall survival (OS) were explored using univariate Cox model. Mean plasma ABI and Δ4A Cmin were 12.6 ± 6.8 ng/mL and 1.6 ± 1.3 ng/mL, respectively. The mean metabolic ratio Δ4A/ABI was of 0.18 ± 0.25. In regard with in vitro pharmacodynamic data, effective plasma concentrations for ABI and Δ4A were reached in 30 patients (83.3%) and only 2 patients (5.6%), respectively. Higher Δ4A Cmin was associated with shorter OS (Hazard ratio, HR 1.54; CI95% 1.06–2.22; p = 0.022) but not with PFS. The HR associated with the metabolic Δ4A/ABI ratio for PFS and OS were 7.80 (CI 95% 1.63–37.38; p = 0.010) and 12.52 (CI 95% 1.95–80.47, p = 0.0078), respectively. The present study shows Δ4A is unlikely to have meaningful contribution to pharmacodynamic activity of ABI in mCPRC, rather that higher plasma Δ4A concentration is associated with worse clinical outcomes. A high Δ4A/ABI metabolic ratio could help to identify mCRPC patients with poorer survival.